Coaching Servant Leadership: Scale Development and Validation - Takamatsu, Shohei (Frontiers in Sports and Active Living, 2022)
This study aimed to develop a valid and reliable scale for measuring coaching servant leadership in different contexts (Japan and the United States). First, potential items were collected in Japan using both deductive (i.e., literature review) and inductive (i.e., surveys among 103 coaches and 34 university students) approaches and narrowed down via content validity assessment by 10 experts. Next, quantitative studies were conducted to validate the scale's construct validity, among 936 high school athletes from Japan. Finally, the scale's applicability to the US context was demonstrated, among 278 university athletes in the US. The analyses resulted in a six-factor model with 17 items to assess coaching servant leadership behaviors: (1) acceptance; (2) shared vision; (3) empowerment; (4) dedication; (5) humility; and (6) winning second. In conclusion, this study developed a coaching servant leadership scale by applying both deductive and inductive approaches and deemed it applicable not only in Japan but also in the US. It is anticipated that future studies will examine the impact of coaching servant leadership on athletes in detail, with findings applied in practice for the development of coaches.